2007
DOI: 10.1128/aac.01186-06
|View full text |Cite
|
Sign up to set email alerts
|

Independent Evolution of Pyrimethamine Resistance in Plasmodium falciparum Isolates in Melanesia

Abstract: Pyrimethamine resistance in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 32 publications
3
46
1
Order By: Relevance
“…5). The haplotype H1, displaying a microsatellite combination of 193-175-201-110 bp on 4 loci, was described previously as the Southeast Asia (SEA) haplotype (19,28). The H19 haplotype, 199-155-201-104, however, had not been reported yet.…”
Section: Identification Of Infection Complexity In Field Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…5). The haplotype H1, displaying a microsatellite combination of 193-175-201-110 bp on 4 loci, was described previously as the Southeast Asia (SEA) haplotype (19,28). The H19 haplotype, 199-155-201-104, however, had not been reported yet.…”
Section: Identification Of Infection Complexity In Field Isolatesmentioning
confidence: 99%
“…This mutant allele evolved and was introduced into other regions in Southeast Asia and Africa through a similar spread pathway of chloroquine resistance (12)(13)(14)(15). Nevertheless, multiple indigenous origins of some single, double, or triple pfdhfr alleles were also reported in Southeast Asia, Africa, South America, and Papua New Guinea (16)(17)(18)(19). To date, the evolution and spread of resistant lineages are traced by the pfdhfr rather than the pfdhps gene, but there are still several surveys that showed that unlike the pfdhfr gene, various sulfadoxine-resistant pfdhps alleles originated independently in each of those areas, including Thailand, Cambodia, Kenya, Cameroon, and Venezuela (17,18,(20)(21)(22).…”
mentioning
confidence: 99%
“…5A) (6,21,58,59) 4-2. Pyrimethamine It has recently been shown that highly pyrimethamine-resistant forms of dhfr (carrying three or more mutations in dhfr) expanded from very limited foci to almost all endemic areas where pyrimethamine/sulfadoxine-resistant parasites are prevalent (7,8,10,60,61) (Fig. 5B).…”
mentioning
confidence: 99%
“…Recent population geneticsbased analyses using microsatellite markers that flank drug-resistance genes have revealed that parasite lineages that are resistant to either chloroquine or pyrimethamine/sulfadoxine are of considerably limited geographic origin, suggesting that these resistant lineages subsequently were dispersed to many endemic areas (6)(7)(8)(9)(10)(11)(12)(13). Here, we review our recent understanding of the evolution of P. falciparum resistance to chloroquine and pyrimethamine/sulfadoxine, with special emphasis on the geographic epicenter of drug resistance, and consider the implications for the development and containment of artemisinin resistance.…”
mentioning
confidence: 99%
“…The Southeast Asian triple mutant dhfr allele AIRNI later spread to Africa, where this is in abundance (7,14,24,28,29). However, there is evidence of indigenous origins of triple mutant dhfr allele AIRNI in several African countries like Kenya, Ghana, and Cameroon (18,19). Two distinct lineages of triple mutant dhfr alleles (RICNI and CICNL) have been reported from South America (8,17,27).…”
mentioning
confidence: 99%